Causal relationship between the allocation of academic failure and level tests to anxiety in High School Student Center of San Marcos - Frisancho León, Augusto Emilio (2014)
The main objective of this study was to determine whether there is relationship between attributional dimensions proposed by Weiner (locus of causality, stability and controllability) and test anxiety. The sample consisted of 206 subjects (61 males and 145 females), Pre-University Center students of San Marcos during the cycles 2010-2011 and Regular Extraordinary 2011-I, who postulated the different careers offered by the Universidad Nacional Mayor de San Marcos. The mean age was 18.1 years. To carry out this investigation we applied the causal dimensions scale (EDC) and the Self-Assessment Inventory Anxiety about exams (IDASE). The results indicate that there is a statistically significant relationship between “stability dimension” of academic failure and the level of test anxiety. We report a direct relationship: as it increases the level of anxiety, the greater the tendency to perceive the causes of failure in exams as stable (persistent over time). There were no statistically significant relationships between the dimensions of locus of causality and controllability and test anxiety. Finally, students with high test anxiety would have a pessimistic attributional style to the failures, unlike students with low test anxiety who exhibit an optimistic attributional style the same.